Breaking Barriers: Improving Patient Adherence to Appointments and Provider Productivity Through Telehealth - Kamalahmadi, Masoud; Zacharias, Christos; Gitlow, Howard; Demers, Stephen; Rubio-Delgado, Cristina; Walker, Katelyn (Production and Operations Management, 2026)
Telehealth services became popular due to the COVID-19 pandemic, yet their operational impacts on healthcare organizations are not well-understood. Patient behaviors can vary significantly between telehealth and in-person appointments, introducing new challenges and opportunities for healthcare delivery. We examine two key behaviors contributing to nonadherence to medical appointments: No-shows and unpunctuality. Analyzing 412,415 telehealth and in-person appointments across a major US medical system from 2020 to 2022, we find that telehealth appointments reduce no-shows by 3.0 percentage points (23.1%) and late-arrivals by 11.4 percentage points (35.6%), indicating significant improvements in appointment adherence. We also find that telehealth is particularly effective in improving adherence to follow-up appointments but may be less suitable for initial consultations with new patients. In addition, telehealth improves adherence most among demographic groups with historically lower in-person attendance—women, racial minorities, Medicaid patients, and younger adults—underscoring its potential to reduce disparities in access. Our analysis suggests that while telehealth may increase patient revisit rates and create extra work for providers, the gains from reduced no-shows, particularly for follow-ups, lead to a net boost in provider productivity. Finally, we explore the best strategies to integrate telehealth into a provider’s daily scheduling template, showing that scheduling telehealth appointments before in-person visits enhances operational efficiency compared to the opposite sequence. Policymakers should recognize telehealth’s capacity to improve appointment adherence, reduce disparities, and enhance productivity, and support its adoption through appropriate regulations. Healthcare organizations should strategically deploy telehealth to address the root causes of patient nonadherence. By offering telehealth appointments to patients facing barriers to in-person care, they can simultaneously optimize both access and productivity.